2008
DOI: 10.1016/j.taap.2008.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-2 and -9 are induced differently by metal nanoparticles in human monocytes: The role of oxidative stress and protein tyrosine kinase activation

Abstract: Recently, many studies have shown that nanoparticles can translocate from the lungs to the circulatory system. As a particulate foreign body, nanoparticles could induce host responses such as reactive oxygen species (ROS) generation, inflammatory cytokine and matrix metalloproteinase (MMP) release which play a major role in tissue destruction and remodeling. However, the direct effects of nanoparticles on leukocytes, especially monocytes, are still unclear. The objective of the present study was to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 73 publications
(74 reference statements)
4
72
1
Order By: Relevance
“…35 Eun-Jung Park and Kwangsik Park indicated that oxidative stress, induced by silica nanoparticles in vivo and in vitro, might have been involved in proinflammatory responses. 36 Other upstream or downstream events, such as heat-shock protein activation, 37 changes in the expression pattern of NADPH oxidase, glutathione peroxidase, and glutathione reductase, 38 apoptosis induction, 39 and kinase activation [40][41][42] have also been shown to be associated with nanoparticle use. In the current study, we found oxidative damage to cells and molecular changes after injection with nanoparticles, which was associated with hepatic and renal tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…35 Eun-Jung Park and Kwangsik Park indicated that oxidative stress, induced by silica nanoparticles in vivo and in vitro, might have been involved in proinflammatory responses. 36 Other upstream or downstream events, such as heat-shock protein activation, 37 changes in the expression pattern of NADPH oxidase, glutathione peroxidase, and glutathione reductase, 38 apoptosis induction, 39 and kinase activation [40][41][42] have also been shown to be associated with nanoparticle use. In the current study, we found oxidative damage to cells and molecular changes after injection with nanoparticles, which was associated with hepatic and renal tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that PC-SOD protects cultured lung epithelial cells from menadione (a superoxide anionreleasing drug)-induced cell death (Tanaka et al, 2010). It has also been reported that oxidative molecules activate MMPs and suppress the expression of ␣1-antitrypsin (Desrochers and Weiss, 1988; Greenlee et al, 2007;Mak, 2008;Wan et al, 2008). Thus, it seems that a PC-SOD-dependent decrease in the level of superoxide anions is responsible for the inhibitory effect of PC-SOD on PPE-induced pulmonary cell death and the protease/antiprotease imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…Since, as stated previously, exposure to metal particles can cause pulmonary alterations (inflammation and fibrosis) the analysis of pulmonary toxicity associated with metallic MNPs is an important issue. Although it was not directly related to the lung, a study by WAN et al [81] provides interesting information about MMP regulation by metallic MNPs in monocytes. This information could be relevant to pulmonary pathophysiology, since one can expect similar results in pulmonary macrophages, which are key cells in the lung response to foreign particles.…”
Section: Manufactured Nanoparticlesmentioning
confidence: 99%
“…This information could be relevant to pulmonary pathophysiology, since one can expect similar results in pulmonary macrophages, which are key cells in the lung response to foreign particles. WAN et al [81] compared the ability of a noncytotoxic concentration of cobalt (Co) and TiO 2 MNPs (5 mg?mL -1 ) to induce the activity and transcription of MMP-2 and -9 in the human monocyte cell line U937. They expected a higher effect of Nano-Co compared with NanoTiO 2 , since they showed in a previous study that Nano-Co caused greater lung injury and inflammation than Nano-TiO 2 , although they have similar diameters [82].…”
Section: Manufactured Nanoparticlesmentioning
confidence: 99%